Analisis Kelayakan Leaflet Keragaman Bakteri di Tanah Gambut Fibrik Pada Submateri Keanekaragaman Hayati Indonesia - Andini, Dini Tiara; Yeni, Laili Fitri; Fajri, Hayatul (Bioscientist : Jurnal Ilmiah Biologi, 2025)
Leaflets are learning media in the form of printed media that provide a summary of learning material to be memorized by students. Leaflet media allows students to learn at their own pace. This study aims to produce products and analyze the feasibility of leaflet media for bacterial diversity in fibric peatlands on the sub-matter of Indonesian biodiversity. The research method used quantitative descriptive method with Content Validity Ratio (CVR) and Content Validity Index (CVI) analysis. Data collection was carried out through leaflet media validation by 3 high school biology teachers and 2 biology education lecturers who assessed the suitability of the research instrument items. The results showed that the leaflet of bacterial diversity in fibric peat soil on the submaterial of Indonesian biodiversity obtained a Content Validity Ratio (CVR) value of 1, indicating high validity, and a Content Validity Index (CVI) value of 1, indicating excellent quality. This means that this leaflet is valid and very feasible to use as learning media in high school in the material of Indonesian biodiversity.